Comparison of ISO 14001:2015 and ISO 45001:2018 Implementation in Coal Mining Sector, Study Case: PT Adaro Energy Tbk, PT Toba Bara Sejahtera Tbk, and PT Indo Tambangraya Megah Tbk - Filson Maratur Sidjabat; Aura Rahardjo Putri; Winda Oktaviani (President University, 2021)
Coal mining is one of the most developed industrial sectors in Indonesia. The quality of natural mineral resources spread across several islands makes Indonesia the 4th coal-producing country in the world. The main component in the coal mining industry activity is changing land and changing the landscape, which causes a high potential impact on the environment, social and community economy. Apart from having a direct effect on the ground, the mining industry is an activity that has a high risk of accidents that result in human injury to death. Therefore, occupational safety and health (K3) are important centres of attention in the mining industry. ISO 45001 and ISO 14001 are international standard certifications that become a component of a company in testing OHS control and environmental management, respectively. Qualitative methods are applied in this study to investigate what programs PT Adaro Energy Tbk, PT Toba Bara Sejahtera Tbk, and PT Indo Tambangraya Megah Tbk in implementing ISO 45001 and ISO 14001. And the result is that Adaro Energy and Indo Tambangraya Megah Tbk have carried out various types of programs to control the environment and prevent accidents for their workers. Meanwhile, Toba Bara needs to improve environmental programs and tighten activities related to training to avoid accidents during operations.